Men's experiences and perceptions of HIV testing services in Gugulethu Township, Cape Town - Ndlovu, Sithembiso Mnqobi Sthandwa (Department of Public Health and Family Medicine, 2017)
South Africa continues to have the highest number of people living with HIV/AIDS in the world. HIV testing remains vital in the prevention and management efforts of the pandemic. Despite the efforts by the government, and local and international organizations to prevent the spread of HIV in men, HIV testing uptake in men continues to remain significantly low in the sub-Saharan Africa, including South Africa. Several factors, including experiences and perceptions of HIV testing services contribute to a low uptake and men's willingness to use HIV testing services in South Africa. This mini-dissertation explores men's experiences and perceptions of HIV testing services from a qualitative perspective. This mini-dissertation is divided in the following three parts. A research protocol (Part A) focuses on understanding men's experiences and perceptions of HIV testing in Gugulethu Township, Cape Town. A literature review (Part B) identifies literature on HIV testing in South Africa, gender norms and their impact on HIV testing uptake, men's perceptions of HIV testing, confidentiality issues, perceived benefits of HIV testing, and gaps in current literature. Lastly, a qualitative journal "ready" manuscript (Part C) focuses on men's experiences and perceptions of HIV testing services in Gugulethu Township, Cape Town. Desirably, this mini-dissertation will inform health interventions that are specific to men's health needs while also aiming to focus on health policies that are inclusive of men. This study will in part address the core issues men encounter when testing for HIV in Gugulethu Township.